2021
DOI: 10.1111/pace.14292
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of left atrial appendage occlusion guided by procedural fluoroscopy only: A pilot study

Abstract: Background Left atrial appendage occlusion (LAAO) is usually performed via the guidance of procedural transesophageal echocardiography (TEE) companied by general anesthesia (GA). Objective To investigate the feasibility and safety of LAAO guided by procedural fluoroscopy only. Methods The patients eligible for LAAO were enrolled into the current study and received implantation of either Watchman device or LAmbre device. The procedure was carried out with procedural fluoroscopy only and no companied GA; the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…Although there have been no articles on the safety and feasibility of DSA alone to guide the combined procedure, the procedure time, fluoroscopy time, total radiation dose, and percentage of fluoroscopic PDL in the LAAO of our study is similar to the previous reports of the LAAO under procedural DSA guidance only 16,19,23 . In the present study, compared with the TEE cohort, the procedure time of the DSA cohort was significantly reduced and there was no significant difference in the complication rate and fluoroscopy time.…”
Section: Discussionsupporting
confidence: 84%
“…Although there have been no articles on the safety and feasibility of DSA alone to guide the combined procedure, the procedure time, fluoroscopy time, total radiation dose, and percentage of fluoroscopic PDL in the LAAO of our study is similar to the previous reports of the LAAO under procedural DSA guidance only 16,19,23 . In the present study, compared with the TEE cohort, the procedure time of the DSA cohort was significantly reduced and there was no significant difference in the complication rate and fluoroscopy time.…”
Section: Discussionsupporting
confidence: 84%
“…The safety and feasibility of MLAAO have previously been evaluated 4–7 . In our study, we found no statistically significant difference in the rate of successful device implantation between the MLAAO group and the SLAAO group.…”
Section: Discussionmentioning
confidence: 42%
“…Emerging evidence suggests that LAAO guided by fluoroscopy guidance only (minimal LAAO [MLAAO]) is also safe and reliable. [4][5][6][7] The aim of this study was to summarize the preliminary results of MLAAO in patients with NVAF under the guidance of fluoroscopy at our center, assess the feasibility and safety of MLAAO and explore its potential benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CHA2DS2-VASc score in the LAmbre group was higher than that in other LAAC group(5.0±1.5 vs 4.1±1.8), which was confirmed by the result. In other studies, 26,28 (Litwinowicz et al 4.0 +-1.1 vs 3.9 +-1.0, Chen et.al. 4.1 +-1.0 vs 3.9 +-1.1, Wang et al 2.8 +-1.0 vs 2.3 +-0.9 ).…”
Section: Discussionmentioning
confidence: 84%
“…Three hundred and nine articles were obtained by online and manual searches. After removing duplicates, screening titles and abstracts, four independent trials [25][26][27][28] contained data for the LAmbre occluder versus other LAAC devices were selected that included 607 patients (142 randomized to the LAmbre occluder and 465 to other LAAC devices). (Figure 1) (as seen in the flow chart).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%